NILAI-NILAI PANCASILA DALAM PENGUATAN KARAKTER MAHASISWA DI ERA DIGITAL: Pancasila Values In Strengthening Student Character In The Digital Era - Loilewen, Aline Febriany (Ganec Swara, 2026)
This study explains that in this digital era, students are required not only to be academically intelligent but also to possess strong character to face the increasingly sophisticated and innovative changes of the times. Pancasila values ​​serve as guidelines for students to use technology wisely and responsibly, always incorporating ethics into their daily lives. This study aims to examine and analyze the challenges and obstacles faced by students in applying Pancasila values ​​in the digital era, and how these values ​​are implemented in their lives. This study uses empirical research, namely research based on the actual implementation of Pancasila values ​​in students' lives in the digital era. The results indicate that students must be ethical, critical, and have character amidst the rapid influence of technology and information in the digital era. Students must be wise, responsible, and ethical by using Pancasila values ​​as a guideline for their lives in the digital era